2016
DOI: 10.1038/nm.4134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CBLB protects from lethal Candida albicans sepsis

Abstract: Fungal infections claim an estimated 1.5 million lives each year. Mechanisms that protect from fungal infections are still elusive. Recognition of fungal pathogens relies on C-type lectin receptors (CLRs) and their downstream signaling kinase SYK. Here we report that the E3 ubiquitin ligase CBLB controls proximal CLR signaling in macrophages and dendritic cells. We show that CBLB associates with SYK and ubiquitinates SYK, dectin-1, and dectin-2 after fungal recognition. Functionally, CBLB deficiency results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 56 publications
0
112
1
Order By: Relevance
“…Of note, all antifungal drugs target fungal growth in the host. However, there is increasing and compelling evidence that modulating the amplitude and magnitude of the host inflammatory immune response can be beneficial for the outcome of invasive fungal diseases [6062]. Thus, chromatin-mediated adaptive changes during fungal pathogen host interplay opens new windows of opportunities and may hold great promises for future antifungal drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all antifungal drugs target fungal growth in the host. However, there is increasing and compelling evidence that modulating the amplitude and magnitude of the host inflammatory immune response can be beneficial for the outcome of invasive fungal diseases [6062]. Thus, chromatin-mediated adaptive changes during fungal pathogen host interplay opens new windows of opportunities and may hold great promises for future antifungal drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that inhibition of JNK1 promotes expression of CD23 (a recently discovered CLR), production for nitric oxide and a potent antifungal effect both in vitro and in vivo 117 . E3 ubiquitin ligase CBLB that ubiquitinates SYK, was shown to regulate antifungal immune responses downstream of dectin-1 and dectin-2 (Figure 3) 118,119 . Genetic deletion or peptide-based inhibition of CBLB promoted strong antifungal response, enhanced fungal killing and protected mice during systemic and cutaneous C. albicans infections 118 .…”
Section: Mucosal Immunity To Fungimentioning
confidence: 99%
“…As these CLRs lack a signaling domain, heterodimeric complexes signal via the ITAM-coupled adaptor FcRγ (9). Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
“…Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52). In contrast, TRIM62-mediated CARD9 ubiquitination is essential for BCL10 interactions, NF-κB activation, and defense against candidiasis (53).…”
Section: Introductionmentioning
confidence: 99%